2022
DOI: 10.3390/agriculture12030389
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Imidacloprid and Flupyradifurone Insecticides on the Gut Microbiota of Bombus terrestris

Abstract: Bumblebees are important pollinators for crops and wild flowering plants. Various pesticides have threatened the abundance and diversity of bumblebees. In addition to direct sublethal effects, pesticides may alter the gut microbial communities of bees. Imidacloprid and flupyradifurone insecticides both bind to the nicotinic acetylcholine receptor. However, the latter was assumed to be harmless for honeybees and can even be applied to flowering crops. In this study, we assessed the impacts of these two pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…In particular, bacteria with the potential to support the degradation and detoxification of EB and TE were differentially abundant following such treatment. This is consistent with prior evidence showing that bumblebees exposed to imidacloprid and flupyradifurone exhibit a significant decrease in levels of bacteria involved in carbon metabolism with a concomitant increase in energy metabolism-related bacterial species, with researchers having speculated that the observed drop in carbon metabolism was attributable to a shift towards bacteria capable of increasing energy metabolism to facilitate pesticide detoxification ( Derecka et al 2013 , Zhang et al 2022 ). Indeed, several symbiotic gut microbes in S. frugiperda larvae have been reported to facilitate the degradation of chlorpyrifos, flubendiamid, deltamethrin, lambda-cyhalothrin, spinosad, teflubenzuro, and telufenuron ( Almeida et al 2017 , Gomes et al 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…In particular, bacteria with the potential to support the degradation and detoxification of EB and TE were differentially abundant following such treatment. This is consistent with prior evidence showing that bumblebees exposed to imidacloprid and flupyradifurone exhibit a significant decrease in levels of bacteria involved in carbon metabolism with a concomitant increase in energy metabolism-related bacterial species, with researchers having speculated that the observed drop in carbon metabolism was attributable to a shift towards bacteria capable of increasing energy metabolism to facilitate pesticide detoxification ( Derecka et al 2013 , Zhang et al 2022 ). Indeed, several symbiotic gut microbes in S. frugiperda larvae have been reported to facilitate the degradation of chlorpyrifos, flubendiamid, deltamethrin, lambda-cyhalothrin, spinosad, teflubenzuro, and telufenuron ( Almeida et al 2017 , Gomes et al 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Although flupyradifurone has been developed as a beesafer pesticide, sublethal doses have been found to impact the life of bees in diverse ways. Similar to results described for bumblebees (Zhang et al, 2022), H. truncorum exposed to flupyradifurone presented in a sucrose solution consume as much food solution as the control group indicating these bees are not averse to the compound. Further, honey bees exposed to field realistic doses of flupyradifurone have been shown to have memory and learning problems (Tan et al, 2017;Hesselbach & Scheiner, 2018) and poor coordination probably decreasing flight ability (Tong et al, 2019) and leading to the premature onset of foraging (Hesselbach et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies on honey bees have found that changes in the gut microbiota can drive feeding behavior changes and increase mortality Zheng et al, 2017). Several factors can lead to this microbiota change, including exposure to agrochemicals (Motta et al, 2018;Zhang et al, 2022). However, our results did not corroborate these findings since none of the agrochemicals (CuSO4, glyphosate, and spinosad) shifted the composition of the gut microbiota in terms of richness of bacterial genera in the conditions tested here using P. helleri.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, balanced gut microbiota may provide protection and resilience to pathogens and xenobiotics, but the processes that govern these communities are far from clear in stingless bees (Mockler et al, 2018;. Previous research on the gut microbiota of A. mellifera, Bombus terrestris and Partamona helleri revealed that exposure to agrochemicals has the potential to alter the gut microbiota of exposed bees Motta et al, 2018;Ye et al, 2021;Zhang et al, 2022). Although most data on the microbiota is centered on honey bees and their findings help to understand the role of the microbiota , it is of paramount importance to assess the dynamics of the microbiota in stingless bees.…”
Section: Introductionmentioning
confidence: 99%